A Preventable Cascade: Severe Acute Malnutrition and Bilateral Pneumonia in a Young Infant with Unrecognized Feeding Dysfunction due to Labiopalatoschizis - Aulia Dyanaputri; Cempaka Kesumaningtyas (International Medical Journal Corp. Ltd, 2026)
Introduction: Severe acute malnutrition and pneumonia remain leading contributors to infant morbidity and mortality, particularly in resource-limited settings. Infants with cleft lip and palate are at risk of feeding dysfunction, which may precipitate nutritional decline if not promptly recognized. Case Illustration: A 1-month-26-day-old male infant with complete unilateral labiopalatoschizis presented with progressive shortness of breath and hypoxemia. Anthropometry revealed weight-for-age, length-for-age, and weight-for-length below –3 SD, consistent with severe acute malnutrition of the marasmic type. Feeding history demonstrated inadequate intake and frequent choking without structured feeding modification. Laboratory findings showed anemia and leukocytosis, and chest radiography confirmed bilateral pneumonia. Management included oxygen therapy, intravenous antibiotics, and phased nutritional rehabilitation via orogastric feeding. Discussion: This case illustrates a preventable cascade in which structural feeding impairment led to chronic caloric insufficiency, immune compromise, and severe respiratory infection. The interaction between malnutrition and pneumonia amplified clinical severity. Early feeding counseling and routine growth monitoring might have prevented progression to severe wasting and infection. Conclusion: Infants with labiopalatoschizis require early structured feeding support and close nutritional surveillance to prevent severe acute malnutrition and life-threatening complications such as pneumonia.